Sentencing multiple-versus single-offence cases: does more crime mean less punishment? - Dhami, Mandeep K. (The British journal of criminology, 2022)
The ‘totality principle’ in law aims to show mercy to offenders in multiple-offence (MO) cases and retain ordinal proportionality in punishing those who commit different categories of offence. The effect of this principle in practice, however, is largely unknown. The present study involved an analysis of data released by the Sentencing Council for England and Wales to estimate the prevalence of MO cases and compare the penalties they received against comparable single-offence (SO) cases. MO cases represented approximately half of the cases in the sample which included violent, property, drugs and driving offences. Offence-specific regression analyses revealed that MO/SO case status was not a significant predictor of receiving a custodial sentence or of custody length. Thus, by applying the totality principle, sentencers may be letting MO offenders ‘off lightly’. Potential explanations for this unintentional effect on decision-making lies in how the totality principle is defined and interpreted, and recommendations are made for revising the guideline on application of the totality principle.